CUT-OUT ANIMATION AS A TECHNIC AND DEVELOPMENT INSIDE HISTORY PROCESS - Gökçearslan, Armağan (Journal of Tourism, Sustainability and Well-being, 2018)
Art of animation has developed very rapidly from the aspects of script, sound and music, motion, character design, techniques being used and technological tools being developed since the first years until today. Techical variety attracts a particular attention in the art of animation. Being perceived as a kind of illusion in the beginning; animations commonly used the Flash Sketch technique. And then tools like Magical Lantern, Thaumatrope, Phenakisticope and Zeotrap were developed and started to be used intensely in the first years of the art of animation. Today, on the other hand, the art of animation is affected by developments in the computer technology. It is possible to create three dimensional and two dimensional animations with the help of various computer softwares. Cut-out technique is among the important techniques being used in the art of animation. Cut-out animation technique is based on the art of paper cutting. This study titled “Cut-out Animation as an Technic and Development Inside History Process” will embrace the art of paper cutting, the relationship between the art of paper cutting and cut-out animation, its development within the historical process, animation artists producing artworks in this field, important cut-out animations and their technical properties.